Automated Financial Reporting and AI-Based Insights for MSMEs Using Gemini AI: A Case Study of Cubic Game House - Michael Christano Suryopranoto; Ridwan Sanjaya; Stephani Inggrit Swastini (Soegijapranata Catholic University, 2026)
MSMEs are the backbone of Indonesia’s economy, but many of them still rely on traditional manual accounting systems which are inefficient and prone to errors. General objective of the research is to develop and implement a web based financial management system using Artificial Intelligence to automatically generate financial report and provide business decision support. The methodology of the research in this paper uses a Waterfall model design and development process where Cubic Game House, a business that rents PlayStation console system, as the case study. The app is programmed in React and uses the Next. js framework and TypeScript is used in the user interface, and financial data is saved temporarily in the browser storage. It will connect to Gemini AI’s API to assess transaction details, generate financial analysis, recognize irregular spending behaviours and share practical business tips. It is concluded that the proposed system improves the financial record-keeping, report generation process and data-driven decision making practices of MSMEs. Our research indicates that AI-based financial systems can be feasibly applied in MSMEs with limited technology.